H2O‐Built Proton Transfer Bridge Enhances Continuous Methane Oxidation to Methanol over Cu‐BEA Zeolite. Issue 30 (17th June 2021) - Xu, Ruinian; Liu, Ning; Dai, Chengna; Li, Yan; Zhang, Jie; Wu, Bin; Yu, Gangqiang; Chen, Biaohua
Abstract: Direct oxidation of methane to methanol (DMTM) is a big challenge in C1 chemistry. We present a continuous N2 O‐DMTM investigation by simultaneously introducing 10 vol % H2 O into the reaction system over Cu‐BEA zeolites. Combining a D2 O isotopic tracer technique and ab initio molecular dynamics (AIMD) simulation, we for the first time demonstrate that the H2 O molecules can participate in the reaction through a proton transfer route, wherein the H2 O molecules can build a high‐speed proton transfer bridge between the generated moieties of CH3 − and OH − over the evolved mono(μ‐oxo) dicopper ([Cu‐O‐Cu] 2+ ) active site, thereby pronouncedly boosting the CH3 OH selectivity (3.1→71.6 %), productivity (16.8→242.9 μmol gcat −1  h −1 ) and long‐term reaction stability (10→70 h) relative to the scenario of absence of H2 O. Unravelling the proton transfer of H2 O over the dicopper [Cu‐O‐Cu] 2+ site would substantially contribute to highly efficient catalyst designs for the continuous DMTM. Abstract : H2 O can directly participate in the continuous N2 O‐DMTM reaction through a proton‐transfer‐bridge over the dicopper [Cu‐O‐Cu] site of Cu‐BEA zeolite. This can significantly boost CH3 OH production rate and enhance long‐term reaction stability.